2021
DOI: 10.1007/s12072-021-10266-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of compensated cirrhosis on survival in patients with acute-on-chronic liver failure

Abstract: Background and aims Acute-on-chronic liver failure (ACLF) is considered a main prognostic event in patients with chronic liver disease (CLD). We analyzed the 28-day and 90-day mortality in ACLF patients with or without underlying cirrhosis enrolled in the ACLF Research Consortium (AARC) database. Methods A total of 1,621 patients were prospectively enrolled and 637 (39.3%) of these patients had cirrhosis. Baseline characteristics, complications and mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Liver dysfunction and its related complications, such as portal-systemic shunting, bacterial translocation, and liver cirrhosis-associated immune dysfunction, have been implicated in the occurrence of BIs [ 21 , 22 ]. In patients with severe acute liver inflammation, an excessive hepatic inflammatory response has been found to exhaust the function of immune cells and result in immune paralysis [ 11 ]. These studies suggested that susceptibility to BIs is dependent on the severity of acute and chronic liver injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver dysfunction and its related complications, such as portal-systemic shunting, bacterial translocation, and liver cirrhosis-associated immune dysfunction, have been implicated in the occurrence of BIs [ 21 , 22 ]. In patients with severe acute liver inflammation, an excessive hepatic inflammatory response has been found to exhaust the function of immune cells and result in immune paralysis [ 11 ]. These studies suggested that susceptibility to BIs is dependent on the severity of acute and chronic liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…The World Gastroenterology Organization working party suggested that ACLF be classified into three types according to the underlying chronic liver disease as follows: type A from non-cirrhotic liver disease, type B from compensated cirrhosis, and type C from decompensated cirrhosis [ 10 ]. Recently, a few studies found that patients with ACLF developed from different underlying diseases had different prognoses [ 11 , 12 ]; therefore, it is clinically important to understand the clinical characteristics of patients with ACLF developed from different underlying liver diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of ACLF on cirrhotic and non-cirrhotic patients has varied among different studies. A study conducted by Thanapirom et al in 2021 in 1621 enrolled patients, which evaluated the impact of compensated cirrhosis on survival in patients with ACLF, showed that short-term mortality rates of ACLF in patients without cirrhosis were significantly increased compared to patients with alcoholic liver cirrhosis [148]. Shalimar et al found that alcohol liver injury was an independent risk factor related to increased mortality [149].…”
Section: Prognosis Of Aclfmentioning
confidence: 99%
“…Several previous studies 4, [7][8][9] investigating ACLF heterogeneity have provided clues. However, a survey systemically assessing the differential outcomes of inpatients with CLDs with a wide spectrum of severities and etiologies upon various inciting events is still lacking.…”
Section: Introductionmentioning
confidence: 99%